The Overview of Malaria Cases in Trenggalek District based on The Epidemiological Triangle - Yusuf Budi Maryanto; Yudied Agung Mirasa (Universitas Airlangga, 2019)
Background: Indonesia is one of the countries where 35% of the population lives in areas with a high risk of malaria infection. Trenggalek is one of the malaria-endemic regions in East Java. Purpose: This study aimed to identify the malaria cases in Trenggalek based on the epidemic triangle and identify the vulnerability status of Anopheles vagus mosquito against Permethrin 0.75% in Pandean Village, Trenggalek. Methods: This study is a type of descriptive observational study. The data used in this study is secondary data obtained from the The Center of Environmental Health and Disease Control Agency Surabaya. The data consists of characteristics of malaria cases in Trenggalek  and Anopheles vagus resistance test data against Permethrin 0.75% in Pandean Village, Trenggalek. Results: Trenggalek is considered as low malaria endemicity area, with malaria incidence dominated by imported malaria cases, because recently there is no cases of autochthonous malaria have been found. Data on malaria case trends in 2014-2017 tended to fluctuate, the majority of malaria patients were male group counting of 97.34% which consist of farmers (59.88%) and private sector worker (29.79%). The Anopheles vagus was found 100% death in one hour of the treatment, but there was no death incidence in the control group. Conclusion: Most malaria patients dominated by male, migrant workers, and most of them work as farmers and the private sector which have a high potential for the emergence of autochthonous malaria. Anopheles vagus is still susceptible to Permethrin 0.75% in Pandean Village, Trenggalek